Limit load evaluation of hydraulic actuators. (4th August 2014) - Baragetti, S.; Terranova, A.
Hydraulic actuators are employed in many fields of mechanical and civil engineering because of their low cost and high reliability. Notwithstanding their diffusion, the structural behaviour of the hydraulic actuators seems not to be well understood and the limit buckling load is determined by neglecting the effects induced by friction at the restrained ends, clearance in correspondence of the connection of the rod with the cylinder and rectilinear imperfections. The object of this paper is to investigate the effects caused by friction and clearance in the connection between the rod and the cylinder for hydraulic actuators of the 'plunger rod' kind. Friction at the restrained ends, for the pin connected ends case, is also evaluated.